9, 10‐Dibromo‐N‐aryl‐9, 10‐dihydro‐9, 10‐[3, 4]epipyrroloanthracene‐12, 14‐diones: Synthesis and Investigation of Their Effects on Carbonic Anhydrase Isozymes I, II, IX, and XII. Issue 6 (13th May 2016) - Göksu, Haydar; Topal, Meryem; Keskin, Ali; Gültekin, Mehmet S.; Çelik, Murat; Gülçin, İlhami and Tanc, Muhammet and Supuran, Claudiu T.
Abstract : N ‐substituted maleimides were synthesized from maleic anhydride and primary amines. 1, 4‐Dibromo‐dibenzo[e, h]bicyclo‐[2, 2, 2]octane‐2, 3‐dicarboximide derivatives (4a–f ) were prepared by the [4+2] cycloaddition reaction of dibromoanthracenes with the N ‐substituted maleimide derivatives. The carbonic anhydrase (CA, EC 4.2.1.1) inhibitory effects of the new derivatives were assayed against the human (h) isozymes hCA I, II, IX, and XII. All tested bicyclo dicarboximide derivatives exhibited excellent inhibitory effects in the nanomolar range, with K i values in the range of 117.73–232.87 nM against hCA I and of 69.74–111.51 nM against hCA II, whereas they were low micromolar inhibitors against hCA IX and XII. Abstract : A series of 9, 10‐dibromo‐ N ‐aryl‐9, 10‐dihydro‐9, 10‐[3, 4]epipyrroloanthracene‐12, 14‐diones (4a –f ) were synthesized from N ‐substituted maleimide derivatives and 9, 10‐dibromoanthracene. Compounds4a –f were assayed against human carbonic anhydrases (hCA) IX and XII, which are the two tumor‐associated isozymes, and hCA I and II, which represent the most common off‐targets for the development of selective anticancer CA inhibitors.